A ambição dos Pariwat: consulta prévia e conflito socioambiental - OLIVEIRA, Rodrigo Magalhães de (Universidade Federal do Pará, 2018)
This paper discusses the situational application of the right of free, prior and informed consultation the different ethnic groups in contexts of social and environmental conflicts produced by projects characterized by intense exploitation of territories and natural resources. The dissertation is located in the interdisciplinary field of Legal Anthropology, whose theoretical and methodological contributions help in the understanding of the uses of law, in addition to legal-centered approaches concerned with compliance / non-compliance with state law. Social and environmental conflict, legal sensitivity, legal pluralism and interlegality are the fundamental categories of analysis. Through ethnography of social and environmental conflict surrounding the Hydroelectric Plant São Luiz do Tapajós project, i seek to show that the federal government and the indigenous people Munduruku have differing legal sensibilities about the situational application of prior consultation. The government's legal sensibility and munduruku legal sensisibility adjust to a broader dispute in which different agents compete to regulate ethnic rights globally. The work shows how human rights may be appropriate creatively by ethnically differentiated groups to strengthen their political struggles.